Musa Observatory: Monitoring open access data for the Musa sector. Version Beta - Andrade, Robert Santiago; García, Carolina; García, Jeffrey; Hoyos, Nicolas; Mwanzia, Leroy; Rivera Vasco, Tatiana Carolina; Schiek, Benjamin; Urioste, Sergio (2022)
The Musa observatory is an initiative led by the Foresight and Applied Economics (FAE) team and the Musaceae Program of the Alliance of Bioversity International and the international Center for Tropical Agriculture (CIAT), to establish an information system that provides indicators related to the global Musaceae production context for the benefit of key stakeholders in the sector. It includes data related to the context of Musaceae in each country, production system information, trade, and competitiveness information, Musaceae consumption data, inventory of technologies related to the crop, and recent news.